Effects of non-allelic interactions of O2 and SU2 mutant genes on grain biochemical composition in various corn inbreds - Tymchuk, Dmytro Serhiiovych; Sadovnychenko, Lurii Oleksandrovich; Tymchuk, Natalia Fedorivna; Pasiuga, Olga Serhiivna (Penerbit Universiti Kebangsaan Malaysia, 2023)
The use of combinations of non-allelic mutant genes of the maize endosperm structure creates opportunities for improving the quality of corn grain in comparison not only with forms of the common type but also with monogenic endospermic mutants. In this study, the effect of a combination of mutant genes O2 (Opaque-2) and SU2 (Sugary-2) according to the biochemical composition of the grain was studied. For the research, a series of inbreds - carriers of a combination of mutant genes O2SU2, inbreds - carriers of monogenic mutations O2 and SU2, as well as maize inbreds of the common type of two-year reproduction were used. In the experiments, the content of protein, starch, and oil and the main characteristics of their quality were studied. It was found that the inbred carriers of the O2SU2 combination are superior to the inbred carriers of monogenic mutations O2 and SU2 in terms of complex biochemical characteristics. In comparison with mutants O2 they were distinguished by an increased content of protein (by 12.3% on average), amylose in starch (by 38.9% on average), starch digestibility (by 24.4% on average), oil content (by 18.4% on average) and oleate content in oil (by 29.9% on average). In comparison with the carriers of SU2 mutation, they had a higher content of lysine and tryptophan in the total grain protein (on average, by 19.4% & 14.3%, respectively). The main characteristics of grain quality in carriers of a combination of mutant genes O2SU2 were characterized by quantitative variability, which can modify the effect of non–allelic interaction of mutant genes O2 and SU2. The obtained results indicate the effectiveness of using non-allelic interactions between the O2 and SU2 mutant genes to improve the quality of corn grain.